Biomarker characteristics of basement oils from White Tiger field on the south shelf of Vietnam; Проблемы геологии и освоения недр; Т. 2 - Vu Van Hai (Geology, mining and petroleum engineering (English, German), 2012)
Заглавие с титульного листа